2021
DOI: 10.3390/medicina57121362
|View full text |Cite
|
Sign up to set email alerts
|

Association between Prehospital Hypoxemia and Admission to Intensive Care Unit during the COVID-19 Pandemic: A Retrospective Cohort Study

Abstract: Background and Objectives: The aim of this study was to assess the association between prehospital peripheral oxygen saturation (SpO2) and intensive care unit (ICU) admission in confirmed or suspected coronavirus disease 19 (COVID-19) patients. Materials and Methods: We carried out a retrospective cohort study on patients requiring prehospital intervention between 11 March 2020 and 4 May 2020. All adult patients in whom a diagnosis of COVID-19 pneumonia was suspected by the prehospital physician were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Prehospital hypoxemia, or low oxygen levels, on room air obtained in triage in the Emergency Department or upon admission to the hospital has also been found to be an independent predictor of COVID-19 critical illness, ICU admission and in-hospital mortality [ 26 28 ]. As compared to traditional illnesses where hypoxemia correlates with significant dyspnea, or labored breathing, COVID-19-infected patients seem to have ‘silent hypoxia’ [ 29 ] where profoundly low oxygen levels are not commensurate with the patients’ relatively comfortable clinical appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Prehospital hypoxemia, or low oxygen levels, on room air obtained in triage in the Emergency Department or upon admission to the hospital has also been found to be an independent predictor of COVID-19 critical illness, ICU admission and in-hospital mortality [ 26 28 ]. As compared to traditional illnesses where hypoxemia correlates with significant dyspnea, or labored breathing, COVID-19-infected patients seem to have ‘silent hypoxia’ [ 29 ] where profoundly low oxygen levels are not commensurate with the patients’ relatively comfortable clinical appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a large retrospective observational study showed that the inclusion of blood glucose assessment in the National Early Warning Score (NEWS) was associated with an improved identification of patients at risk of death [29]. In the specific context of COVID-19, dysglycaemia may represent a potential useful prehospital indicator in addition to classic parameters such as respiratory (SpO2, respiratory rate) or hemodynamic parameters [30,31]. This could help reduce ED length of stay by enabling more efficient patient disposition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during the two waves of the pandemic, the organisation of hospitals in the canton of Geneva was reviewed, with the main public hospital (Geneva University Hospitals), which was defined as the “COVID-19 hospital”, receiving all patients with (or suspected of having) COVID-19, and the other hospitals or private clinics mainly receiving patients without COVID-19 [ 26 ].…”
Section: Methodsmentioning
confidence: 99%